2014
DOI: 10.1080/15021149.2014.11434723
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Precision Teaching to Teach Basic Math Facts

Abstract: A Precision Teaching program for basic math facts was designed for students in the 5th, 6th, and 7th grade level in a regular primary school. Forty-eight typically developing students who were nominated by their teacher as falling behind their classmates in multiplication and division participated. Following a randomization there were two groups of 24 each: one that received Precision Teaching and one that received treatment as usual. The Precision Teaching intervention was put in place for 20 minutes each sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…In an 8‐week study of fifth‐, sixth‐, and seventh‐grade students, Strømgren et al () tested for endurance and stability with math facts using fluency criteria of 70 correct responses per minute. Participants in the experimental group received a PT frequency building intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In an 8‐week study of fifth‐, sixth‐, and seventh‐grade students, Strømgren et al () tested for endurance and stability with math facts using fluency criteria of 70 correct responses per minute. Participants in the experimental group received a PT frequency building intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Endurance tests lasted 90 s. Stability tests lasted 30 s while students listened to music in headphones as a distractor. Although most students only reached between 55 and 65 in the experimental condition, Strømgren et al () reported that participants who scored above 50 correct responses per minute in the experimental condition maintained scores more reliably on the stability and endurance assessments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This more accurately reflects how people learn (Johnson & Street, 2013). These charts have been successfully used to monitor student progress with basic facts in studies with participants similar in age to those in this study (Chiesa & Robertson, 2000;Gallagher, 2006;Strømgren, Berg-Mortensen, & Tangen, 2014). PT's emphasis on progress monitoring makes it particularly suitable for use within the post-action stage of SRL programs.…”
Section: Instructional Approaches To Enhance Multiplication Fluencymentioning
confidence: 99%